Providing researchers with the skills and competencies they need to practise Open Science: Open Science Skills Working Group Report - Brennan, Niamh (European Commission DG-RTG, 2017)
Open Science is transformative to the research landscape, allowing research to be carried out with a high degree of transparency, collegiality, and research integrity. For Open Science to become a reality researcher need appropriate discipline-dependent skills training and professional development at all stages of their research careers. To facilitate this, the Steering Group on Human Resources and Mobility (SGHRM) Working Group (WG) on ‘Education & Skills’ worked with a specific mandate to propose recommendations to ensure that researchers in Europe have appropriate skills and competences to practice Open Science. The overarching goal is to ensure that OS skills become an integral and streamlined component of the standard education, training and career development paths of researchers, and if possible even at earlier career stages, in schools and universities.
GOLD i.e. published open access
Keywords: Skills; Training; Open Science; Open Access; Open Science; Research careers; Research skills; Scholarly communication